THE POSITION OF IDDAH NAFKAH AS A WIFE'S RIGHT AS A RESULT OF DIVORCE REVIEWED FROM CIVIL LAW - Puteri Amanda; Rabiah Z Harahap (RADJA PUBLIKA, 2026)
Divorce has legal consequences for economic rights, one of which is the iddah maintenance. This study aims to analyze the legal status of iddah maintenance as a wife's right, evaluate its regulation and implementation, and identify its legal implications from a civil law perspective. Using a normative legal research method with a statute approach, this study found that civil law views iddah maintenance as an obligation arising from law. However, the effectiveness of its fulfillment is still hampered by weak enforcement mechanisms and low legal awareness of ex-husbands. The results of the study suggest protecting the subjective rights of wives through stronger civil law instruments, such as collateral seizure, in order to achieve distributive justice.